Effect of Independence, Time Budget Pressure, and Auditor Ethics on Audit Quality - Handoko, Bambang Leo; Pamungkas, Hertin Restu (International Journal of Psychosocial Rehabilitation, 2020)
Audit quality is very important because the results of the audited financial statements will be used as a decision-making tool by users of financial statements, such as investors and creditors. Audit itself is a service, which quality is influenced by people who carry out the audit process, namely the auditor. Our research studies what factors can influence the quality of audits. We use three independent variables: independence, time budget pressure and audit ethics. Our research is quantitative research; the data we use are primary data from the results of questionnaires. Our respondents are auditors who work at public accounting firms in Jakarta. We use an analysis technique called ordinary least square, we test using regression analysis to determine whether the variable is influential or not. Our results state that auditor independence and ethics influence while time budget pressure does not affect audit quality